Multiple Components of the Outflow in the Protostellar System HH 212: Outer Outflow Shell, Rotating Wind, Shocked Wind, and Jet - J. A. López-Vázquez; Chin-Fei Lee; Hsien Shang; Sylvie Cabrit; Ruben Krasnopolsky; Claudio Codella; Chun-Fan Liu; Linda Podio; Somnath Dutta; A. Murphy; Jennifer Wiseman (The Astrophysical Journal)
We present the Atacama Large Millimeter/submillimeter Array Band 7 observations of the CO ( J = 3−2) line emission of the protostellar system HH 212 at ∼24 au spatial resolution and compare them to those of the SiO ( J = 8−7) and SO ( J = 8−7) line emission reported in the literature. We find that the CO line traces four distinct regions: (1) an outer outflow shell, (2) a rotating wind region between the SiO and CO shells, (3) the shocked and wide-angle inner X-wind inside a SiO shell, and (4) the jet. The origin of the CO outer outflow shell could be associated with the entrained material of the envelope, or an extended disk wind. The rotating wind, which is shocked, is launched from a radius of 9–15 au, slightly exterior to that of the previously detected SO shell, which marks the boundary where the wide-angle X-wind is interacting with and shocking the disk wind. Additionally, the SO is found to be mixed with the CO emission within the thick and extended rotating wind region. The large-scale CO-shocked wind coexists with the SO emission near the upper portion of the inner shocked region converged on top of the inner SiO knots. The CO jet is traced by a chain of knots with roughly equal intervals, exhibiting quasiperiodicity, as reported in other jets in the literature.